Concepções e práticas de professores sobre o lúdico nas escolas organizadas por ciclos de formação humana - Bressan, João Carlos Martins (2014)
This research seeks to understand how teachers' conceptions about the ludic interferes/affect their educational practices. The research produced under this perspective denote considerable theoretical framework about the themes: game, fun, plaything. However, when direct analysis regarding the theoretical productions elucidates on the ludic, there is a limited amount of production. Among other factors highlight the ambiguous character of the terminology, which makes it somewhat unveiled by teachers who intend to experience it in the school environment. Another relevant issue is the theorization of educational concepts and practices of the teachers surveyed. The purpose was to subsidize the presentation of these concepts to enable analyzes that include data collected which in turn aim to meet the objective of this research which relies on: Evidence understanding of the concepts of playfulness of teachers working in the first cycle of basic education in schools statewide network of county Rondonópolis/MT. Which parses the following specific objectives :To investigate teachers' conceptions about the ludic; Analyze/understand how these concepts influence the educational practice of teacher; Reflect on the importance of ludic activities in the context of the classroom early years of elementary school. To do so, is guided initially presented the concept of conceptions Ponte (1992), Silva (2009) and Garnica (2008). Regarding explanations about the concept of playfulness is anchored in Huizinga (2000) , Almeida (2003), Marcellino (2003) and Kishimoto ( 2011a) , and the term developments in playfulness and ludic activities has its foundations in Luckesi (2002) D' Avila (2006), Brougère (2011), D' Avila (2006) Kishimoto ( 2011b , 2011c): Regarding the importance of playfulness in educational practice the following authors were referenced. This study used qualitative research approaches and interpretive method, the reference chosen was based on Bogdan and Biklen (1994), Flick (1999), Vianna (2003), Richardson (1999). We analyzed the contents of the data collected from three teachers of the early years of elementary school, about playfulness and its importance in the teaching-learning process through data collection instruments that constitute observation and interviews. The process of data analysis and considerations show the design of the teachers on the play, through their educational practices. Unveil that broadly the teachers believe in the importance of a differentiated educational practice that considers the play in the relations of teaching and learning, however, expose weaknesses on the theoretical understanding of the subject, which shows some conflicts that relate to their pedagogical practice, but also to the perception that management and co-workers have regarding their professional practice. This research allows to recognize the play is evidenced in a time of transition from childhood education for elementary school thus constitutes important elements for a reflection on the educational practice and teacher formation for that period.